The Role of Co-Creation Value and Innovation Capability In Building Sustainable Competitive Advantage In Teaching Hospitals - Rian Puspitasari; Sartika Gani; Muthmainna Sri Dewi; Mifta Annajasi Muslimin; Laode Hidayat (Politeknik Kesehatan Kemenkes Mamuju, 2026)
Increasing competition in Indonesia’s hospital industry requires teaching hospitals to adopt strategies beyond internal innovation by emphasizing collaborative value creation with stakeholders through Co-Creation Value (CCV).This study examines the direct effect of CCV on Sustainable Competitive Advantage (SCA) and its indirect effect through Innovation Capability (IC) at Universitas Hasanuddin Teaching Hospital. A quantitative explanatory design was applied using survey data from 263 employees selected through proportional stratified random sampling. Data were analyzed using covariance-based Structural Equation Modeling (SEM) with AMOS, and construct validity was assessed through Confirmatory Factor Analysis (CFA). CCV had a significant positive effect on IC (β = 0.869) and SCA (β = 0.880). However, IC did not have a significant effect on SCA (β = 0.020). The mediating effect of IC on the relationship between CCV and SCA was weak (indirect β = 0.018). CCV is a more dominant determinant of SCA than IC. In the context of a teaching hospital, sustainable competitive advantage is shaped more strongly by collaborative value creation involving patients and stakeholders than by innovation capability alone. Therefore, hospital management should prioritize co-creation strategies by strengthening stakeholder collaboration and patient engagement, while aligning innovation initiatives with organizational strategy, patient needs, and long-term institutional objectives.